THE CORRELATION BETWEEN PHYSICAL LEARNING ENVIRONMENT AND STUDENTSâ€™ CRITICAL THINKING AT ENGLISH EDUCATION DEPARTMENT OF UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Fitri Hidayati (PBI 15 UMY 026, 2015)
*26 Physical learning environment is believed to be able to aid students in learning. This study is aimed at investigating the physical learning environment and studentsâ€™ critical thinking at English Education Department of Universitas Muhammadiyah Yogyakarta. Also, this study is expected to find the correlation between learning environment and studentsâ€™ critical thinking. The researcher used quantitative approach and designed this study as correlational research. The sample of this study was 79 students taken from 100 of the whole student batch 2012 at English Education Department. The data of learning environment and studentsâ€™ critical thinking were obtained by questionnaire items and analyzed using SPSS version 19 through descriptive and inferential statistics. The result showed that the learning environment at English Education Department of Universitas Muhammadiyah Yogyakarta is in sufficient category. The mean value for data of learning environment is 2.64, which means that English Education Department has adequate learning environment. The level of studentsâ€™ critical thinking at English Education Department is in moderate category with the 2.39 mean value. It means that the critical thinking of English Education Department students of Universitas Muhammadiyah Yogyakarta is in intermediate level. The last finding is on the correlation between learning environment and studentsâ€™ critical thinking. The finding shows that there is statistically significant correlation between learning environment and studentsâ€™ critical thinking in very weak level ( r = 0.186 ). Therefore, the alternate hypothesis (Ha) â€œthere is a statistically significant correlation between learning environment and studentsâ€™ critical thinking at English Education Departmentâ€ is accepted and the null hypothesis (H0) is rejected